Analisis Implementasi Holistik Integratif TK Islam Khaira Ummah, Padang - Lina Lina; Hadiyanto Hadiyanto (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
The background of this research shows that education for students is the responsibility of parents. The purpose of this study is to analyze the integrative holistic implementation by using the CIPP approach. When the parents work and cannot take care of their children, they trust the caregivers or adults at home without consideration of the caregiver's educational background. The teacher believes that the obligation to care is the responsibility of the family or parents. Teachers in schools are also obliged to teach their children to read, write and count. The integrative holistic early childhood development program has a strong legal basis, namely Presidential Regulation No. 60 of 2013. Thus, integrative holistic early childhood development must be carried out in a special early childhood education unit, such as the Khaira Ummah Islamic Kindergarten in the city of Padang. The obligation to implement an integrative holistic early childhood development program, according to the mandate in Presidential Regulation No. 60 of 2013 as a whole is concluded that even though some programs have not developed optimally, most programs have been managed holistically and integratively.